Free daycare policies, family choices and child development - Busse, Anna; Gathmann, Christina (Journal of economic behavior & organization, 2020)
Over recent decades, many governments have expanded state-subsidized daycare for preschool children. Using the staggered introduction of free universal daycare for children between the ages of two and six, we show that free daycare increases attendance only among 2-3-year-old children. There is no effect for older children for which attendance rates have been high even before the reforms. Similarly, labor market attachment increases for mothers with 2-3-year-olds, while mothers of 4-6-year-olds respond mostly at the intensive margin. Short-run development for the average child is largely unaffected by the reforms. Responses and short-run benefits are much more pronounced for poorer and low-skilled families than for the average household. Hence, despite being a universal program, free daycare helps to level the playing field for children from disadvantaged backgrounds - provided the policy is focused on age ranges with low prior attendance.
Gesehen am 24.11.2020
We would like to thank the editor and two anonymous referees, Silke Anger, Simona Bejenariu, Elizabeth Cascio, Gerard van den Berg, Nezih Guner, Tuomas Kosonen, Katharina Spiess, Gesine Stephan, Katharina Wrohlich as well as participants at the Society of Labor Economists (SOLE), European Associ- ation of Labor Economists (EALE), European Economic Association, the Verein für Socialpolitik, University of Heidelberg, University of Mannheim, University of Cologne, Center for European Economic Research (ZEW), German Institute for Economic Research (DIW), the Spring Meeting of Young Economists for helpful comments and suggestions. Anna Hautmann provided excellent research assistance. All remaining errors are our own